Potency of Radical Scavenging Activity and Determination of Total Phenolic Content of Five Ethanolic Extract of Rhizome Zingiberaceae Family - Muhammad Da'i; Didiek Setiawan; Rosita Melannisa (Indonesian Society for Cancer Chemoprevention, 2013)
Several studies show that some plants and fruits could protect human body from free radical danger exposure. Zingiberaceae family has some chemical substances that have antiradical activity, such as phenolic compound and flavonoid. The aim of this study is to determine the correlation of total phenolic compound towards its antiradical activity. Antiradical activity assay was determined by DPPH method (1,1 difenil-2-pikrilhidrazil). The total phenolic compound is determined by spectrofotometry using Folin-Ciocalteu reagent and counted as GAE (Gallic Acid Equivalent). Based on this study, the total phenolic concentration of ethanolic extract of jahe (Zingiber officinale (L.) Rosc), kencur (Kaemferia galanga L.), lengkuas (Languas galanga), lempuyang gajah (Zingiber littorale) and lempuyang pahit (Zingiber americana) is 73.99 mg/g; 23.848 mg/g; 37.841 mg/g; 49.725 mg/g and 40.802 mg/g respectively. The radical scavenging activity (IC50) of jahe (27.38 µg/mL), lengkuas (93,27 µg/mL), lempuyang pahit (105,08 µg/mL), meanwhile lempuyang gajah and kencur show low activity of radical scavenging.Keywords: Zingiberaceae, total phenolic compound, antiradical, DPPH